2019
DOI: 10.1097/meg.0000000000001395
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of antitumour necrosis factor agents and vedolizumab in ulcerative colitis

Abstract: Introduction Antitumour necrosis factor (TNF) agents and vedolizumab are used to treat ulcerative colitis (UC) but the response is variable and there is little data on comparative effectiveness. Apart from previous exposure to anti-TNF agents, predictors of response have not been identified. We aimed to (i) compare the efficacy of anti-TNF agents and vedolizumab in UC and (ii) investigate the utility of clinical and biochemical parameters in predicting response. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 20 publications
0
9
0
1
Order By: Relevance
“…Some studies in IBD patients have shown that previous anti-TNF therapy is a risk factor for failure of treatment with vedolizumab [13,14,[50][51][52][53][54][55][56], regardless of the reason for anti-TNF discontinuation; conversely others have shown that the response to vedolizumab is independent of previous anti-TNF failure [57][58][59][60][61][62][63]. Nevertheless, it should be noted that, to date, most of the patients who received vedolizumab treatment, both in randomised controlled trials and in clinical practice, were anti-TNF experienced [64].…”
Section: Efficacy Of Vedolizumab In Anti-tnf Naïve Vs Anti-tnf Exposed Patientsmentioning
confidence: 99%
“…Some studies in IBD patients have shown that previous anti-TNF therapy is a risk factor for failure of treatment with vedolizumab [13,14,[50][51][52][53][54][55][56], regardless of the reason for anti-TNF discontinuation; conversely others have shown that the response to vedolizumab is independent of previous anti-TNF failure [57][58][59][60][61][62][63]. Nevertheless, it should be noted that, to date, most of the patients who received vedolizumab treatment, both in randomised controlled trials and in clinical practice, were anti-TNF experienced [64].…”
Section: Efficacy Of Vedolizumab In Anti-tnf Naïve Vs Anti-tnf Exposed Patientsmentioning
confidence: 99%
“…Even though numerous studies have demonstrated that biological agents can reverse the inflammation in IBD, a recent large retrospective real‐world study from the United States shows that more than half of patients with IBD discontinue treatment with their initial biological within the first 12 months 44 . Information on which biological agent to use as second‐line treatment after initial anti‐TNF failure is sparse and previous observational studies comparing the effectiveness of a second anti‐TNF agent vs vedolizumab are limited by small sample size or study design 29‐34 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, anti‐TNF treatment was restricted to adalimumab and most patients treated in clinical practice would not have been eligible for the VARSITY trial, where inclusion was restricted to patients of certain ages, degrees of disease activity, comorbidity, prior and concurrent medications. Real‐world studies comparing the effectiveness of an anti‐TNF agent vs vedolizumab show conflicting data and some include a mixture of patients with different anti‐TNF exposure, making the results difficult to interpret 29‐34 …”
Section: Introductionmentioning
confidence: 99%
“…VDZ was superior to adalimumab with respect to achievement of clinical remission and endoscopic improvement but not corticosteroid‐free clinical remission 6 . However, another study indicated a comparable efficacy of VDZ and anti‐TNF agents among UC patients 7 . Also, compared to anti‐TNF agents, VDZ has a rather limited effect on extraintestinal manifestations of IBD 8 .…”
Section: Introductionmentioning
confidence: 97%
“…6 However, another study indicated a comparable efficacy of VDZ and anti-TNF agents among UC patients. 7 Also, compared to anti-TNF agents, VDZ has a rather limited effect on extraintestinal manifestations of IBD. 8 In summary, it remains unclear if certain classes of medications would be more favourable compared to others as first-line therapy, since reliable predictive biomarkers are still lacking.…”
Section: Introductionmentioning
confidence: 99%